Prevention of experimental venous thrombosis induced by contrast medium in the rat - Maffei, Francisco Humberto de Abreu [UNESP]; Rollo, Hamilton Almeida [UNESP]; Fabris, Viciany Erique [UNESP] (My University, 1980)
In order to assess experimentally the usefulness of some procedures employed in man to prevent venous thrombosis following phlebography, thrombosis was induced in rats using sodium diatrizoate in a temporarily isolated segment of a jugular vein. The prevention of thrombosis was attempted by washing out the vein with physiologic saline or saline plus heparin or by injecting saline plus heparin in the opposite jugular vein. Thrombosis occurred in all animals in the control group and in the group treated with saline alone. Both treatment schemes with heparin significantly reduced the incidence of thrombosis, the wash out with heparin being more effective than systemic heparin.
Keywords: diatrizoate; heparin; sodium chloride; animal experiment; blood and hemopoietic system; deep vein thrombosis; drug induced disease; intravenous drug administration; peripheral vascular system; phlebography; rat; thrombosis; thrombosis prevention; vein thrombosis; Animal; Contrast Media; Diatrizoate; Drug Combinations; Heparin; Infusions, Parenteral; Jugular Veins; Rats; Sodium Chloride; Thrombosis